PEMANFAATAN MOTOR SERVO SEBAGAI PENGGERAK CCTV UNTUK MELIHAT ALAT-ALAT MONITOR DAN KONDISI PASIEN DI RUANG ICU - Hilal, Ahmad; Manan, Saiful (Gema Teknologi, 2013)
Ahmad Hilal, Saiful Manan, in paper use servo motor as a CCTV driver to see monitoring equipment and conditions of patients in the icu room explain thatservo motor is a motor with a closed feedback system in which the position of the motor will be communicated back to the control circuit in the servo motor, servo motor is able to work both directions (clockwise and belawanan clockwise) in which the direction and angle of the rotor movement can controlled only by providing PWM signal duty cycle settings on the control pin. In the servo motor function of this type is only capable of moving in either direction (CW and CCW) with respective deflection angle reaches 90 Â° so that the total deflection angle of the center - right -kiri adalah180 Â°. Part of the servo motors consist of a potentiometer which functions as a regulator of the servo movement of a large pulse is given, the internal gear serves as a torque amplifier dc servo motors, dc motors as the driving part that converts electrical energy into motion, as well as a control circuit servo motor driver function to process the data input pulses into motion. Servo motors used to drive the CCTV, in order to see the health of the patient monitoring devices as instructed. The servo motor voltage of 5 volts dc power supply from PC. Servo motor movements influenced the input pulse, to round to the right then it takes the pulse of more than 1,5ms, for the leftist movement takes the pulse of less than 1,5ms and at the center position or silence takes input pulse of 1.5 ms with a delay of 20 ms. Servo motors work processes in order to move that the serial data input from the PC, the serial data into the ATMEGA 8 for processing, so that the serial data is converted into binary data through IC74595 as servo motor driver, to output one of IC74595, the servo motor can move, because inflows along with pulses to the servo motor control circuit. Keywords: DC servo motors, Power Supply, IC74595, ATMEGA 8